2022
DOI: 10.1109/access.2022.3169147
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things (IoT) and Machine Learning Model of Plant Disease Prediction–Blister Blight for Tea Plant

Abstract: Crop plant diseases are a significant threat to productivity and sustainable development in agriculture. Early prediction of disease attacks is useful for the effective control of the disease by taking proactive actions against their attacks. Modern Information and Communication Technologies (ICTs) have a predominant role in Precision Agriculture (PA) applications to support sustainable developments. There is an immense need for solutions for the early prediction of the disease attack for proactive control aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Guava is also included. The compilation included both pictures collected from the Internet as well as those shot by the contributors themselves [19,20]. The images were rotated, modified affinely & perspectively, and had their intensities changed.…”
Section: Literature Surveymentioning
confidence: 99%
“…Guava is also included. The compilation included both pictures collected from the Internet as well as those shot by the contributors themselves [19,20]. The images were rotated, modified affinely & perspectively, and had their intensities changed.…”
Section: Literature Surveymentioning
confidence: 99%
“…The dataset consisted of 36,258 images. A more recent study that used Multiple Linear Regression (MLP) reported 91% accuracy in identifying blister blight in tea plants [34], while another recent study reported the use of CNN algorithm to detect 13 different diseases achieved precision of 96.3% [35].…”
Section: A Related Workmentioning
confidence: 99%
“…This action will provide power to the fan, enabling it to start and exhaust air from the greenhouse or enclosed area. Similarly, if the gas concentration falls below the threshold, turn off the GPIO pin connected to the fan, stopping the fan and conserving power [11].…”
Section: Ventilation Systemmentioning
confidence: 99%